Pengaruh Kemenarikan Desain Website dan Kemudahan Informasi terhadap Persepsi Konsumen dan Keputusan Pembelian Belanja Online - Maisara Batubara; Sunaryo Sunaryo; Ichsan Anshori Tambunan (JaManKu: Jurnal Manajemen dan Kewirausahaan, 2022)
This study aims to determine (1) the influence of the attractive website design on customer perception, (2) the influence of ease of information on customer perception, (3) the influence of the attractive website design on online purchasing decisions, (4) the influence of ease of information on online purchasing decision, (5) the influence of customer perception on the online purchasing decision. The population of this study is the customer of Kyou Hobby Shop in Medan. The number of samples taken in this study was 101 respondents. As a suggestion that can be put forward, that is in kyou.id to maintain the attractiveness of website design starting from the aspect of visual attractiveness and layout design that combines color combinations must be more creative and attractive that will make consumers not feel bored to access kyou.id for a long time.